2020
DOI: 10.3390/en14010079
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation of Hydraulic Power Take-off Unit Parameters for Wave Energy Converter Device Using Non-Evolutionary NLPQL and Evolutionary GA Approaches

Abstract: This study is concerned with the application of two major kinds of optimisation algorithms on the hydraulic power take-off (HPTO) model for the wave energy converters (WECs). In general, the HPTO unit’s performance depends on the configuration of its parameters such as hydraulic cylinder size, hydraulic accumulator capacity and pre-charge pressure and hydraulic motor displacement. Conventionally, the optimal parameters of the HPTO unit need to be manually estimated by repeating setting the parameters’ values d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Thus, this is an innovative method for effective treatment for toxic phenol contaminant elimination from aqueous solutions. Jusoh et al [14] applied two major kinds of optimization algorithms (Quadratic Lagrangian (NLPQL) and evolutionary Genetic Algorithm (GA)) on the hydraulic power take-off (HPTO) model for the wave energy converters (WECs). The optimal simulation results showed that the performance of HPTO units has significantly improved up to 96% and 97%, respectively, in regular wave conditions.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this is an innovative method for effective treatment for toxic phenol contaminant elimination from aqueous solutions. Jusoh et al [14] applied two major kinds of optimization algorithms (Quadratic Lagrangian (NLPQL) and evolutionary Genetic Algorithm (GA)) on the hydraulic power take-off (HPTO) model for the wave energy converters (WECs). The optimal simulation results showed that the performance of HPTO units has significantly improved up to 96% and 97%, respectively, in regular wave conditions.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%
“…This Special Issue of Energies on the subject of "Green Energy Technology" contains the successful invited submissions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. A total of 17 technical papers that cover diversified green energy technology-related research have shown critical results and contributed significant findings in biofuel production [1], energy-saving in buildings [2], wind energy [3], energy policy [4], electricity supply [5], a thermal-hydraulic system [6], fluidized bed reactor [7], green-supply chains [8], SI engine [9], renewable energy grid [10], kinetic energy harvest [11], green hydrogen utilization [12], water conservation [13], hydraulic power [14], Illumination Performance in buildings [15], community renewable energy [16], and heat transfer [17].…”
Section: Introductionmentioning
confidence: 99%
“…To find the optimal global solution of the optimization objective, the nonlinear sequential quadratic programming (NLPQL) algorithm is used to iteratively find the optimal combination of parameters that can maximize the engine output power. The algorithm applies a quadratic Taylor series to expand the objective function and linearize the constraints, transforming the original nonlinear problem into a quadratic programming problem [43,44].…”
Section: Design Optimization Modelmentioning
confidence: 99%
“…The WEC concept based on [20] is considered in the present study. The simplified concept is shown in Figure 1A.…”
Section: Design Of Wec With Hpto Unitmentioning
confidence: 99%
“…Recently, several kinds of research into the HPTO in WAB-WECs have been published for various objectives, for example in [15][16][17][18][19][20][21]. From the literature, most of the studies have concentrated on the performance of the HPTO unit without investigating the influence of the important parameters of HPTO.…”
Section: Introductionmentioning
confidence: 99%